NILAI-NILAI PENDIDIKAN KARAKTER DALAM PROGRAM INTERPROFESSIONAL EDUCATION (IPE) - Rahman, Faisal (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2022)
The development of technology and the challenges of the times that are getting bigger with the dissemination of information that is so massive can affect the formation of the character of the younger generation so that a program is needed that can shape the character of the younger generation. Character education is an important alternative solution that can be implemented in the era of globalization given the rapid flow of information and the influence of foreign cultures that are increasingly unstoppable with digital technology. One alternative that can be implemented to be able to carry out character education is Interprofessional Education (IPE), which has been widely applied in the world of health. This article provides a conceptual framework for how Interprofessional Education (IPE) can be developed and applied in character education because the basic competencies contained in Interprofessional Education (IPE) have values ​​and principles that are in line with character education. In this article, the author explores the values ​​and principles in Character Education in the Interprofessional Education (IPE) program.